Supercritical CO2 extraction from endemic Corsican plants; comparison of oil composition and extraction yield with hydrodistillation method. (July 2017) - Mouahid, Adil; Dufour, Cyril; Badens, Elisabeth
Highlights: Extraction from Corsican endemic plant. Comparison of supercritical CO2 and hydrodistillation methods. Extraction of bioactive molecules. Determination of oils compositions. Abstract: Generally speaking, essential oils (EOs) and components of interest are extracted from plants using hydrodistillation (HD), steam distillation or organic solvent methods The Supercritical CO2 (SC-CO2 ) extraction technique is a good alternative to the three previously mentioned methods as it is able to be applied at temperatures close to ambient and shows no toxicity to humans or the environment. The aim of this study is to investigate the ability of supercritical CO2 extraction to extract bioactive components from four Corsican endemic plants: Rosmarinus officinalis, Juniperus communis ssp nana, Helichrysum italicum and Pistacia lentiscus . After the extracts were analyzed by gas chromatography, it would appear that SC-CO2 is the most adapted process for the extraction of such components of interest as verbenone, germacrene D, bornyl acetate, ferruginol, trans-caryophyllene, elemol, γ-cadinene, geraniol or β-eudesmol in higher quantity. The SC-CO2 extraction curves were obtained using two models published by Sovová. These models give access to complementary information and help to estimate the values of some important data such as the possible maximal extraction yield for Helichrysum italicum and the end of the extraction period.